2005
DOI: 10.3184/095422905782774883
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metal species in decomposed municipal solid waste

Abstract: Heavy metal speciation studies on municipal solid waste samples collected from Kodungaiyur dumpsite in Chennai, India, were carried out for Cu, Ni, Pb, Zn, Cr, Fe, Mn and Cd. Three samples were collected at depths of 0 -1 m, 1 -2 m and 2 -3 m, and analyzed. X-ray diffraction studies showed the presence of montmorillonite, illite, quartz and calcium carbonate minerals. The Tessier method was used to fractionate the metal content into exchangeable, acid extractable, reducible and oxidizable fractions. Residual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 21 publications
0
37
1
Order By: Relevance
“…Unlike control soil sample that has only Pb, Cu and Zn concentrations as 0.003, 0.125, 0, 0 and 0.063 mg/kg respectively (Amusan et al, 2005;Esakku et al, 2003). Only Lead concentration recorded in the contaminated soil (wet, dry and amended) exceeded the permissible limit of Federal Ministry of Environment (FMEnv) and World Health Organization (WHO) while Zinc, Chromiun, Copper and Cadmium were within the limits.…”
Section: Heavy Metalsmentioning
confidence: 84%
“…Unlike control soil sample that has only Pb, Cu and Zn concentrations as 0.003, 0.125, 0, 0 and 0.063 mg/kg respectively (Amusan et al, 2005;Esakku et al, 2003). Only Lead concentration recorded in the contaminated soil (wet, dry and amended) exceeded the permissible limit of Federal Ministry of Environment (FMEnv) and World Health Organization (WHO) while Zinc, Chromiun, Copper and Cadmium were within the limits.…”
Section: Heavy Metalsmentioning
confidence: 84%
“…The conventional method developed by Tessier, et al, (1979) was followed for the sequential extraction. The residual and total metal contents were determined in aqua regia digest (Esakku, et al, 2005;Shrivastava and Banerjee, 1998). The residual fractions of the sequential extracted samples and the total metal content in fresh samples were extracted with aqua regia using a behrotest digester block with a TRS 200 microprocessor controller.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies have reported low leaching rates of heavy metals over relatively long periods of time (Esakku, Palanivelu, & Joseph, 2003;Gould et al, 1990;Kjeldsen et al, 2002;Reinhart & Basel Al-Yousfi, 1996;Ross, Harries, Revans, Cross, & NATHANIEL, 2000).…”
Section: Metals Contentmentioning
confidence: 99%